Evaluating the Managing Medicines for People With Dementia Website Version 2. Issue 1 (January 2019) - Burns, Pippa; Mullan, Judy; Gillespie, Robyn; Harrison, Lindsey; Win, Khin Than; Baker, Amanda; Traynor, Victoria; Kostovski, Catherine; Thomas-Lee, Rhett Jay; Gleeson, Holly; Horne, Frances; Velev, Zoran
Abstract : The Managing Medicines for People With Dementia version 2 website was developed in three languages, English, Italian, and Macedonian, to assist informal caregivers in the task of managing medications. Medication management is a complex task with potentially high stakes health outcomes, including hospitalization and death. A mixed-methods evaluation was carried out. A survey was available to site users and Web log data were collected over a 3-month period. Subsequently, the quality and suitability of the information and readability and usability of the Web site were evaluated. Focus groups and interviews were conducted with end users from all three language groups. Data collected from the evaluation surveys during the pilot test showed that users were generally satisfied with site usability (77%). The results of the readability testing indicate that future versions could be improved. Feedback from the focus groups and interviews was generally positive. The use of multiple methodologies provided comprehensive testing that is likely to have identified the majority of usability issues. Ways in which the site can be maintained with up-to-date information and be promoted to the target population, informal carers, need to be explored.